2018
DOI: 10.1089/bfm.2017.0159
|View full text |Cite
|
Sign up to set email alerts
|

Milk Volume at 2 Weeks Predicts Mother's Own Milk Feeding at Neonatal Intensive Care Unit Discharge for Very Low Birthweight Infants

Abstract: Continued provision of MOM at NICU discharge can be predicted in the first 14 postpartum days on the basis of achievement of CTV. We posit that CTV can serve as a quality indicator for improving MOM feedings in the NICU and that lactation support resources should target this early critical postbirth period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 40 publications
3
61
2
3
Order By: Relevance
“…Lactation support is vital in the first few days after birth, especially for mothers of premature infants ( 5 ). The volume of feeds required by premature infants are minimal, Even a small amount of DHM per infant could provide enough volume to allow the mother the time to come-to-volume, resulting in her own milk being available for her infant ( 22 ).…”
Section: Background For the Development Of This Decision Treementioning
confidence: 99%
See 1 more Smart Citation
“…Lactation support is vital in the first few days after birth, especially for mothers of premature infants ( 5 ). The volume of feeds required by premature infants are minimal, Even a small amount of DHM per infant could provide enough volume to allow the mother the time to come-to-volume, resulting in her own milk being available for her infant ( 22 ).…”
Section: Background For the Development Of This Decision Treementioning
confidence: 99%
“…Systems are needed that support mothers to develop their own milk supply and prioritize their milk for their infants. Research has shown that mothers who reach full volume by 14 days post-delivery, estimated as 500 mL of breast milk per day, are more likely to be able to continue breastfeeding at discharge ( 22 ). Robust hospital policies and guidelines are needed to ensure all efforts have been made to prioritize mother's own milk and support maternal lactation, not only prior to the allocation of DHM, but routinely during the infant's hospitalization.…”
Section: Background For the Development Of This Decision Treementioning
confidence: 99%
“…Early and frequent expression also increases the probability of establishing a full milk supply adequate to meet the infants’ needs. There is strong evidence that the frequency of breast expressions per day is positively related to both daily and weekly milk production 6–9. Therefore, the common advice is to encourage mothers of preterm infants to expression 8–10 times day and double pumping when possible.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, health care professionals should be educated on the important role of human milk in reducing the risk for developing comorbidities in preterm infants and should promote and protect breastfeeding, supporting the mothers particularly in the first 14 days after delivery. Indeed, during this window of time, the preterms' mothers are at higher risk for producing an insufficient volume of milk, thus experiencing the so called "impaired coming to volume", which negatively affects the long term lactation outcomes [10] in the broadest context possible. Future research on how tp implement the starting and the duration of human milk feeding in preterm infants is needed.…”
mentioning
confidence: 99%